The relationship between mild cognitive impairment and postoperative delirium undergoing total knee arthroplasty: The PNDABLE study - Wang, Bin; Mu, Chuanlin; Tang, Xinhui; Wang, Fei; Zhang, Gaofeng; Wang, Jiahan; Dong, Rui; Lin, Xu; Bi, Yanlin (Frontiers in Aging Neuroscience, 2022)
Background Patients undergoing surgery are at a higher risk of developing postoperative delirium (POD) as a result of anesthesia and surgical procedures. This study examined the association between POD and mild cognitive impairment (MCI) and whether MCI influences POD through the core pathology of POD. Methods We enrolled Chinese Han patients undergoing unilateral total knee arthroplasty (aged 50–90, weighing 50–80 kg, and using ASAI-II), combined with epidural anesthesia between October 2020 and June 2021. All the participants were assessed using Winblad's criteria for diagnosing MCI on pre-operation and using the Confusion Assessment Method (CAM) and the Memorial Delirium Assessment Scale (MDAS) postoperative 1–7 days (or before discharge) for diagnosing POD by an anesthesiologist. Cerebrospinal fluid (CSF) biomarkers of POD were measured by enzyme-linked immunosorbent assay (ELISA). To examine the mechanism by which POD pathologies affect cognition, causal mediation analyses were performed. Results POD incidence was 20.2%, including 32.5% in the MCI group and 12.4% in the non-mild cognitive impairment (NMCI) group. The MCI and CSF levels of T-tau and P-tau were risk factors, and the CSF levels of Aβ42, Aβ42/ T-tau, and Aβ42/ P-tau were protective factors in POD (p < 0.05). Part of the effects of MCI on cognition can be attributed to amyloid pathology and tau. Conclusion MCI may be a reasonably good prognostic factor in POD development. Overall, amyloid pathology and tau protein might partially mediate the influence of MCI on POD. Clinical trial registration www.clinicaltrials.gov, identifier: ChiCTR2000033439.